INTERNET OF THINGS: APPLICATIONS, BARRIERS AND ITS STATUS - Sowmya, G; Kumar, B.Akash; Naganjaneyulu, K.V; Chandrakanth, S (IJRDO -Journal of Computer Science Engineering, 2015)
Over a decade Internet has been playing major role in the process of digitalization and improving the standards of communication levels of the people. Internet is continuing to be more strong and persistent with the introduction of the wireless broad band connectivity. With the help of this internet, a new revolutionary technology called Internet of Things (IOT) is implemented where everything in this world is connected to internet. Although a lot of work has been done in the working implementation of IOT it is still facing many difficulties in the real world environment. This paper gives the information about employment opportunities generated by IOT and present trends of IOT business levels and role of government to implement it. .